Chief Executive Officer Collectivism and Corporate Pollution Abatement Behavior: Evidence From Industrial Firms in China - Wang, Shumin; Huang, Yikun; Zhong, Chao; Li, Boxi (Frontiers in Psychology, 2022)
This paper examines the relationship between CEOs' collectivistic cultural background and corporate pollution abatement behavior among industrial firms in China. Using hand-collected data on birthplaces of CEOs of the industrial firms, we provide robust evidence that CEOs born in provinces with a higher level of collectivistic culture promote corporate pollution abatement performance. The paper further shows that firms exhibit significant differences in their emission reduction behavior when firms are subjected to environmental regulation shocks: firms with collectivistic CEOs tend to reduce more pollution than firms with individualistic CEOs without sacrificing their firms' production.